A presença italiana em nomes de ruas de Belo Horizonte: passado e presente - Zuleide Ferreira Filgueiras (2011)
The present dissertation main goal conduct linguistic research, focusing on the lexicon in urban toponymy Belo Horizonte analyzing, among all the publics streets that are at city, those 183 streets wich received anthroponyms Italian origin. City planned to be the seat thegovernment of Minas Gerais Belo Horizonte received on your land at the very beginning of their construction in the late XIX century, Italian immigrants who came Attracted by job opportunities. The purpose of this research is to demonstrate that the study of places namesallows rescue part of local history and culture of a community, since the toponyms beyond to perpetuate characteristics of the physical environment (vegetation, hydrology, geomorphology, fauna, etc.), shows marks of social history (ethnic, migration processes, system of grow of population of an administrative region). The theoretical and methodological framework is grounded in concepts of DAUZAT (1926) and DICK (1990a,1990b and 2004) and the concepts of environment, according to SAPIR (1969). In light of sociolinguistics, modeled Labovian, we start in the present and we went back to past. First, we consulted all the names of common grounds in the city of Belo Horizonte and selecting,among them, the toponyms motivated by anthroponyms of Italian origin. We conduct research on historical documentation centers and with relatives of the honored personalities. We had access to all maps and plans of streets, avenues, alleys and squares and photographed all thenameplates present in these streets. Oral interviews conducted with the goal of researching cases of variation, change and retention of language and also to know the representation of these names to the people that living in these streets. We built to each italian anthroponym atoponym card. The results obtained through the survey enabled us to have ac cess to a historical past, economic and, of the social development of Belo Horizonte show that the statecapital was strongly influenced by the presence of Italian immigrants although little known today among the their habitants. Other relevant results were the significant presence of place toponomy in parallel, revealed by 57.92% of respondents who cited other names by which thestreets are known, and the high rate of variation and change, 83.61%, a figure above the 16.39 % retention.